Unusual initial presentation of prostate adenocarcinoma with inguinal lymph nodes metastases: a case report - Sofronievska Glavinov, Maja; Jovanovikj, Rubens; Majstorov, Venjamin; Burneski, Jovo; Nikolovski, Andrej (Oxford University Press (OUP), 2024)
The presence of lymph node metastases in prostate adenocarcinoma is a poor prognostic sign, and mortality rates are often high. Inguinal lymph node metastases are an unusual presentation of advanced disease, and they can be easily misinterpreted with other diseases. We present a case of a 63-year-old patient with no previous symptoms and signs of prostate disorder with a right-sided inguinal lump and abdominal pain. The CT scan showed right inguinal and retroperitoneal lymphadenopathy. Elevated PSA serum levels, digital rectal examination, and skeletal scintigraphy with 99mTc-MDP favored the diagnosis of metastatic prostate adenocarcinoma. Since the patient denied prostate biopsy, a dissection of the right inguinal nodes was performed. Histopathological findings confirmed metastatic prostate adenocarcinoma. The treatment was hormonal and bisphosphonate therapy, with objective posttreatment improvement. Based on this case, it can be concluded that inguinal and generalized lymphadenopathy are potential initial manifestations of metastatic prostate adenocarcinoma in male patients.
Keywords: prostate adenocarcinoma; inguinal lymphadenopathy; metastases; case report